1998
DOI: 10.1103/physrevlett.80.173
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Mixed-Valence and Kondo-Lattice State in TmTe at High Pressure

Abstract: Neutron diffraction experiments on TmTe at pressures up to 7 GPa are reported. The semiconductor-to-metal transition occurring at 2 GPa in this compound is accompanied by the appearance of strong ferromagnetic exchange interactions producing a Curie temperature as high as 14 K. This behavior is characteristic for the incipient mixed-valence regime just above the transition pressure and traced back to the release of a small concentration of free charge carriers in the material. The steep decrease of both the Cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The sided Nd:yttrium-aluminum-garnet laser large sample size could allow the use of heating to 3700 K at 3 GPa of a graphite additional types of analysis, such as neusample sandwiched between two layers of tron diffraction (28), neutron scattering NaCl platelets. We also heated moissanite (29), inelastic x-ray spectroscopy, x-ray anvils in air to 1400 K for 36 hours without Compton scattering. nuclear magnetic resdamage, showing that the moissanite anvil onance (30), and ultrasonic interferometry is useful for high P-T experiments with (31.…”
Section: Moissanite: a Window For High-pressure Experimentsmentioning
confidence: 99%
“…The sided Nd:yttrium-aluminum-garnet laser large sample size could allow the use of heating to 3700 K at 3 GPa of a graphite additional types of analysis, such as neusample sandwiched between two layers of tron diffraction (28), neutron scattering NaCl platelets. We also heated moissanite (29), inelastic x-ray spectroscopy, x-ray anvils in air to 1400 K for 36 hours without Compton scattering. nuclear magnetic resdamage, showing that the moissanite anvil onance (30), and ultrasonic interferometry is useful for high P-T experiments with (31.…”
Section: Moissanite: a Window For High-pressure Experimentsmentioning
confidence: 99%
“…In addition a crystallographic phase transition has been reported at ϳ8 GPa, from the NaCl structure to a tetragonal phase. [8][9][10] The optical properties of TmSe 1−x Te x alloys have also been measured, 11 in particular the Kerr rotation spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Pressures up to 15 GPa (Cornelius et al, 1996) and temperatures of 30mK have been reported (Webb et al, 1976). Neutron diffraction is very sensitive to the magnetic order (Goncharenko & Mirebeau, 1998), but the determination of the magnetic moment variations remains limited in precision (Link et al, 1998). Although most published work is reported for pressures below 20 GPa, recent studies up to 50 GPa in a DAC at liquid He temperature have been performed (Goncharenko & Mirebeau, 1997).…”
Section: Introductionmentioning
confidence: 99%